PELATIHAN MEMBUAT ROTI UNTUK MENINGKATKAN EKONOMI KELUARGA DI DESA KEMLAKAGEDE - Prita Agustina; Faisal Basri; Isabela; Muhammad Reza Fahlepi (IAIC (Institut Agama Islam Cirebon), 2022)
The problems that occurred in Kemlakagede Village were a challenge for the KKM (Student Work College) team to overcome the low entrepreneurial spirit in the area. Where in partner areas, there are still many housewives who still have a lot of free time, therefore it is necessary to empower women, especially housewives who are no longer working to be given training on bread making. With this training, it is hoped that it will be able to encourage the ability and motivation of partners to become entrepreneurs. The purpose of implementing Community Service is to be able to provide new ideas about entrepreneurship and motivate housewives to want to be entrepreneurs. Where the target to be achieved is that the community becomes creative and can make bread products to be used as an idea to become an opportunity for entrepreneurship in making bread. The method of implementing community service activities is providing training and discussions about the process of making bread. While the implementation of community service activities is carried out in the even semester of 2022. The results and outputs obtained by the service are housewives are able to make their own bread to be used as a potential for self-employment so that they can improve the family economy.